Jorge E. Domínguez. Educación, dependencia tecnológica y planificación. México : Centro de Estudios Educativos, A. C., 1969. 107 p. - García Rocha, Adalberto (Estudios Demográficos y Urbanos, 1970)
JORGE E. DOMÍNGUEZ, Educación, dependencia tecnológica y planificación. México, Centro de Estudios Educativos, A. C, 1969.